Diagnostic markers. - Seow, Heng Fong; Abdullah, Maha (2009)

(untitled)
There are disclosed protein molecules that provide noel targets for the development of therapeutics of human leukemia. These protein molecules are forkhead transcription factor (FKHR) and proapoptotic member of the Bcl-2 family (bad) of the phosphoinositide 3-Kinase pathway and p38 and JUN-terminal kinase (Jnk) of the mitogen-activated protein kinase pathway.